Inscribed landscapes in the Black Desert: Petroglyphs and kites at Wisad Pools, Jordan. (13th May 2020) - Hill, Austin Chad; Rowan, Yorke M.; Wasse, Alexander; Rollefson, Gary O.
Abstract: Petroglyphs are well known in the Negev, eastern and southern Jordan, and the Arabian Peninsula. Intensive documentation of hundreds of petroglyphs at the site of Wisad Pools in the Black Desert of eastern Jordan records animals, humans, hunting traps and geometric designs, connecting people and places to the larger landscape. These were recorded at the landscape scale with drones and photogrammetry, and the local scale through the construction of a database combined with GPS recording and terrestrial photogrammetry. Petroglyphs of animals and hunting traps are significant because the site is located within a landscape that includes enormous and enigmatic hunting traps (desert kites). Mapping these depictions highlights typological distribution, association of types, and relation to landscape features as well as the topography of the basalt boulders on which they were pecked. The depictions of animals and hunting traps provide clues about the use of desert kites, the social role of hunting, communal gatherings, and feasting in the region.